Assessing value creation and value capture in digital business ecosystems - SHARMA, Ravi S. (Institutional Knowledge at Singapore Management University, 2010)
Interest in business modeling of technology enterprises – the activity of designing the architecture for revenues, costs, products and/or services delivery and the overall value of an enterprise – has risen to prominence with the global crossing of the Internet chasm. However, as several studies have pointed out (c.f., Osterwalder, Pigneur & Tucci, 2005; Teece 2010; Zott & Amit, 2010), the investigations of business models and their fit with the strategy of an enterprise, have received little scholarly attention. In this article we formulate a framework, called ADVISOR, for modeling the business strategies of enterprises in the Interactive Digital Media (IDM) industry. We focus on how IDM de novo firms could use the ADVISOR framework to assess their value creation and capture potentials in their respective digital business ecosystems.